The Extremes - Priest C. Christopher (London, Scribner, 1999)
Granted compassionate leave after her husbands death by shooting, Teresa Simons goes to England and begins to unravel the circumstances behind a seemingly unprovoked shooting in a small seaside town. Using virtual reality Teresa discovers something terrifying - about herself and the future.